2019
DOI: 10.3390/molecules24193420
|View full text |Cite
|
Sign up to set email alerts
|

Xanthommatin is Behind the Antioxidant Activity of the Skin of Dosidicus gigas

Abstract: Marine bioactive compounds have been found in very different sources and exert a very vast array of activities. Squid skin, normally considered a discard, is a source of bioactive compounds such as pigments. Recovering these compounds is a potential means of valorizing seafood byproducts. Until now, the structure and molecular properties of the bioactive pigments in jumbo squid skin (JSS) have not been established. In this study, methanol–HCl (1%) pigment extracts from JSS were fractionated by open column chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…with antioxidants were obtained from squid skin using acidified ethanol (Aubourg et al, 2016) and acidified methanol (Chan-Higuera et al, 2019a, c). Moreover, the main ommochromes identified in squid skin pigmented extracts are xanthommatin and dihydroxhantommatin (Chan-Higuera et al, 2019c).…”
Section: Chemical Structure and Antioxidant Activity Of Cephalopod Skmentioning
confidence: 99%
See 1 more Smart Citation
“…with antioxidants were obtained from squid skin using acidified ethanol (Aubourg et al, 2016) and acidified methanol (Chan-Higuera et al, 2019a, c). Moreover, the main ommochromes identified in squid skin pigmented extracts are xanthommatin and dihydroxhantommatin (Chan-Higuera et al, 2019c).…”
Section: Chemical Structure and Antioxidant Activity Of Cephalopod Skmentioning
confidence: 99%
“…1 H-NMR spectroscopy analysis was employed to provide information regarding the chemical composition and conformation of the obtained pigments (Figure 2). In a recent study, using 1 H-NMR spectra Chan-Higuera et al (2019c) revealed the presence of xanthommatin (11-(3-amino-3-carboxypropanoyl)-1-hydroxy-5-oxo-5H-pyrido[3,2 a]phenoxazine-3-carboxylic acid) and its derivatives (hydro-and dihydroxanthommatin) in antioxidant pigments from the squid skin. These pigments are considered to be tryptophan-derived metabolites that come from the kynurenine pathway (Daniels & Reed, 2012).…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…(2) Reducing Power Assay. Reducing power of each test compound was tested according to Oyaizu [21,22], where 1 ml of different concentrations of each of andrographolide (1 nM-1 mM) prepared in ethanol were mixed with 5 ml of a solution containing equal volumes of potassium ferricyanide [K 3 Fe(CN) 6 ] and PBS (200 mM and pH 6.5). e mixture was incubated for 20 min at room temperature, and then 2.5 ml of 10% TCA (w/v) was added to the mixture, and the mixture was centrifuged at 3000 rpm for 10 min.…”
Section: Materials and Chemicals Rpmi-1640 Medium Albu-mentioning
confidence: 99%
“…e extent of the absorbance augmentation is directly proportional to the reducing power of the compound. Results are expressed as % of absorbance augmentation [21,22].…”
Section: Materials and Chemicals Rpmi-1640 Medium Albu-mentioning
confidence: 99%
“…Peptides derived from a tryptic hydrolysate of jumbo squid skin exhibited strong inhibition of lipid peroxidation that was much higher than the natural antioxidant α-tocopherol [15]. Skin molecules as xanthommatin also showed in vitro antioxidant effects [16]. Additionally, cytotoxic, antimicrobial, anti-biofilm, angiotensin converting enzyme (ACE)-inhibitory peptides, and anti-tumoral properties have been demonstrated for skin ink and the hydrolyzed skin of different squid species [14,17,18].…”
Section: Introductionmentioning
confidence: 99%